Learning RNA Isolation on Oral Swab Sample on Bats in Bandar Lampung Urban Areas - Elfita Nova Yunior; Elly Lestari Rustiati; Enny Saswiyanti; Emantis Rosa; Priyambodo Priyambodo; Eko Agus Srihanto; Dian Neli Pratiwi (Ann Publisher, 2026)
Background. Bats are recognized as important reservoir hosts for various zoonotic viruses, including coronaviruses, posing potential public health risks, particularly in urban environments where human–animal interactions are frequent. Aims. This study aimed to evaluate the effectiveness of RNA isolation from oral swab samples of bats captured in urban areas of Bandar Lampung, Indonesia, as a preliminary step for molecular detection of viral pathogens. Methods. Sampling was conducted using mist nets in the University of Lampung area, followed by oral swab collection and preservation in viral transport medium. RNA isolation was performed through four main stages: lysis, binding, washing, and elution. The quality of RNA was assessed using agarose gel electrophoresis, while the quantity was measured using a Qubit Fluorometer. Result. A total of six bats were successfully sampled, consisting of Cynopterus brachyotis and Cynopterus sphinx. Qualitative analysis revealed a single thin, luminescent band in all samples, indicating suboptimal RNA integrity. Quantitative results showed RNA concentrations ranging from 0.58 to 2.03 ng/µL, with three samples falling within the acceptable range (1.8–2.0 ng/µL), suggesting adequate RNA purity. Variations in RNA quality and concentration were likely influenced by factors such as incubation duration and sample handling, potentially leading to contamination or degradation. Conclusion. In conclusion, RNA isolation from bat oral swabs in urban areas is feasible; however, protocol optimization is necessary to improve RNA integrity and yield. High-quality RNA is essential for reliable downstream molecular analyses, including viral detection and surveillance of zoonotic diseases